Air pollution and sport performance: is the respiratory system the weakest link? - Bougault, V. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Climate change is accompanied by a growing release of pollutants in the air we breathe. In some parts of the world, pollution levels are dangerously high on a daily basis, while in other countries, the frequency and duration of peaks of pollution are increasing. Several events, such as the forest fires during the 2020 Melbourne tennis tournament or ozone pollution during the 1984 Los Angeles Summer Olympic Games, have raised concerned about the safety for athletes to compete in polluted environments. Many athletes indeed complained of respiratory symptoms - sometimes severe - during these events, which prompted some to withdraw from competition. Since the 1984 Olympic Games and the well-known Los Angeles ozone fog, air measurements are taken to check pollution levels in the run-up to major sporting events. During the last Summer Olympic Games (Tokyo 2020), the organizing committees took measures to reduce car traffic and improve air quality. Such approach is however rarely in place for lower profile events. In this context, it is reasonable to wonder about the physiological and performance consequences of acute exposure to air pollutants. Due to the complexity of the research process, there is still very little literature on the subject. However, with the development of new tools for measuring pollutants, research under ecological conditions is growing. In this talk, we will identify first the main pollutants that athletes encounter while exercising indoor and outdoor. We will then present the known effects of these pollutants on sports performance, and explore the possible mechanisms leading to performance decrement. We will finally discuss how the respiratory system - as the point of entry of the pollutants into the body - copes with these environmental insults, and consider preventative strategies to reduce pollution-induced respiratory issues.